Agreement For Kidney Transplant Between An International Donor And An Indonesian Recipient In Compliance With Indonesian Health Legislation - Geta Ilham Adi Prasetyo; Habib Adjie; Utari Dewi Fatimah (Magister Kenotariatan Universitas Pasundan, 2023)
The arrangement between an international donor and an Indonesian recipient requiring a 'kidney' or any other organ for human organ transplantation represents a private understanding between the involved parties. This stems from the fact that therapeutic agreements and health-related legislations do not govern relationships established through private arrangements between donors and recipients. An incident was reported wherein an individual generously donated their kidney to a recipient in need and received compensation as an expression of gratitude. Although the donor's actions in this case went against the humanitarian principles endorsed by health laws, they did not contravene the legal framework. This serves as evidence that Indonesian regulations currently lack provisions addressing organ transplants conducted by unrelated living donors, resulting in the absence of legal safeguards for such donors.